Hi all, here is my question:
x = x+1 -1
3 2
I cannot figure it out at all so if anyone can help me with the solution not just the final answer would be appreciated.
Use brackets, it makes you work infinity easier to read. Better yet, use LaTeX
If, as I assume, the question is $\displaystyle \dfrac{x}{3} =\dfrac{x+1}{2} - 1$ then multiply through by the LCD of 1, 2 and 3.
We can check it, multiply all the terms with a factor 6 (LCM of 1,2 and 3) therefore we get:
$\displaystyle 2x=3(x+1)-6$
$\displaystyle \Leftrightarrow 2x=3x+3-6$
$\displaystyle \Leftrightarrow -x=-3 \Leftrightarrow x=3$
So recheck your calculations.